Zasoby osobiste a niepełnosprawność sensoryczna - Szabała , Beata (Studia Edukacyjne, 2017)
Personal resources are an important factor contributing to health and the quality of life. Their role is even greater in difficult situations, such as the ones experienced by individuals with visual and auditory impairments/deficits. The research was to diagnise personal resources of adults with isual and auditory impairments/deficits. These resources were analysed in terms of the meanig of life, self-assessment, and social support. Research was conducted with 80 respondents aged 20-30, where 40 respondents were visually impaired, and 40 respondents were auditorily impaired. Instruments used: The Meanig of Life Scale by J.C. Crumbaugh and K.T. Maholicka, A Questionnaire of Social Support by J.S. Norbeck, a Self-Assessment Scale by W.H. Fitts, and author’s own questionnarie. Research findings reveal certain divergences between groups in terms of the analysed resources, with the most significant ones in the sphere of self-assessment.